Giant Ferroelectric Resistance Switching Controlled by a Modulatory Terminal for Low-Power Neuromorphic In-Memory Computing - Xue, Fei (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.